Optimalisasi Pemanfaatan Alokasi Dana Desa Melalui Program Pemberdayaan Masyarakat - Dewi Maya Sari; Zulfan Zulfan (Puslatbang KHAN, 2019)
The village funds allocation over the past four years has been employed more for physical development rather than for community empowerment programs. The village fund ultilization for the needs of empowering human resources was still minimum. For this reason, it is necessary to optimize the use of Village Fund Allocation (ADD) for the field of community empowerment. This study used a qualitative method with a descriptive approach. The results of this study indicated that optimizing the use of village fund allocation through community empowerment programs can be realized by the establishment of Village-Owned Enterprises (BUMDes), the establishment of a Village Community Empowerment Cadre (KPMD), and Community Learning Capacity Building (Community Center).